2006
DOI: 10.1073/pnas.0605588103
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mapping of genetic regions associated with apomixis inHieracium

Abstract: Although apomixis has been quoted as a technology with the potential to deliver benefits similar in scale to those achieved with the Green Revolution, very little is currently known of the genetic mechanisms that control this trait in plants. To address this issue, we developed Hieracium, a genus of daisies native to Eurasia and North America, as a genetic model to study apomixis. In a molecular mapping study, we defined the number of genetic loci involved in apomixis, and we explored dominance and linkage rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 56 publications
6
127
0
5
Order By: Relevance
“…However, observations on various plant species are consistent with the idea that the transition to parthenogenesis (apomixis) may require only a small number of key mutations. As in D. pulex, meiosis suppression in plants is typically female specific, with males producing functional haploid sperm (Grimanelli et al 2001;van Dijk and Bakx-Schotman 2004;Catanach et al 2006;Noyes et al 2007;Ravi et al 2008). In addition, female meiosis suppression in plants is frequently associated with a single dominant factor (which does not rule out the presence of a tight linkage group of several loci), and the ability to initiate development in the absence of fertilization is conferred by one additional factor at most (again, possibly a tight cluster of genes).…”
Section: Discussionmentioning
confidence: 99%
“…However, observations on various plant species are consistent with the idea that the transition to parthenogenesis (apomixis) may require only a small number of key mutations. As in D. pulex, meiosis suppression in plants is typically female specific, with males producing functional haploid sperm (Grimanelli et al 2001;van Dijk and Bakx-Schotman 2004;Catanach et al 2006;Noyes et al 2007;Ravi et al 2008). In addition, female meiosis suppression in plants is frequently associated with a single dominant factor (which does not rule out the presence of a tight linkage group of several loci), and the ability to initiate development in the absence of fertilization is conferred by one additional factor at most (again, possibly a tight cluster of genes).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Taraxacum and Erigeron species, two independent loci have been identified that control diplospory and parthenogenesis (Van Dijk et al 1999;Noyes and Rieseberg 2000). Similarly, apospory and parthenogenesis are controlled by two independent loci in Hypericum, Poa, Hieracium, and Cenchrus species (Albertini et al 2001;Catanach et al 2006;Schallau et al 2010;Conner et al 2013). Genetic studies in Hieracium, which is also capable of fertilization-independent endosperm formation, have revealed that this trait can also segregate independently of the other two apomictic components (Ogawa et al 2013).…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…Instead, the megaspore mother cell undergoes meiosis and as aposporous initial cells are not formed, a functional haploid embryo sac develops, and the egg and central cell form an embryo and endosperm, respectively, in the absence of fertilization. Deletion of both the LOA and LOP loci results in complete reversion to sexual development (Catanach et al 2006;Koltunow et al 2011). Apomixis in aposporous Hieracium therefore seems to be superimposed on the sexual pathway, suggesting that apomixis may redirect the fate of cells with gametic potential, rather than being a detached and completely independent pathway ).…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…(Pessino et al 1998) and P. squamulatum (Ozias-Akins et al 1998) where apomeiosis and autonomous embryogenesis are controlled by a single dominant locus. However, it is difficult to rationalise when multiple independent loci control the different components, which is the case for species such as T. officinale (van Dijk et al 1999), E. annus (Noyes 2005) and H. caespitosum (Catanach et al 2006). The chance that two mutations could occur almost simultaneously in a plant or population and subsequently give rise to viable apomictic progeny is highly unlikely (Asker and Jerling 1992).…”
Section: Did Apomixis Arise Through Mutation Of Sexual Genes?mentioning
confidence: 99%
“…If the hybridisation theory is correct, then the genomic regions controlling the initiation of apomixis might simply reflect key regulators of the sexual pathway that are mis-expressed in time and space. This may be an important point to consider as mapping and mutagenesis approaches in Pennisetum, Hieracium and Taraxacum and other apomictic species approach the core regions controlling apomixis in these plants (Vijverberg et al 2004;Akiyama et al 2005;Catanach et al 2006).…”
Section: Interspecific Hybridisation May Lead To the Initiation Of Apmentioning
confidence: 99%